2019
DOI: 10.3389/fpsyt.2019.00844
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Programs for Early Recognition of Severe Mental Disorders: Recommendations From an Italian Multicenter Project

Abstract: The onset of mental disorders often occurs in adolescence or young adulthood, but the process of early diagnosis and access to timely effective and appropriate services can still be a challenge. The goal of this paper is to describe a pilot case of implementation of the ultra-high-risk (UHR) paradigm in six Italian departments of mental health employing an integrated approach to address clinical practice and service organization for youth in a broader preventive perspective. This approach entailed the integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“… Domains Interventions Demographic Service characteristics • Anti-stigma and youth-friendly community setting and service delivery. [ 17 , 20 , 35 , 44 , 52 , 53 , 65 ] • Flexible outreach approach to enhance engagement of young people. [ 37 , 65 ] • Presence in catchment areas with high levels of ethnic minorities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Domains Interventions Demographic Service characteristics • Anti-stigma and youth-friendly community setting and service delivery. [ 17 , 20 , 35 , 44 , 52 , 53 , 65 ] • Flexible outreach approach to enhance engagement of young people. [ 37 , 65 ] • Presence in catchment areas with high levels of ethnic minorities.…”
Section: Resultsmentioning
confidence: 99%
“…[ 30 ] Selective strategies and corresponding good mental health domains • Recreational therapy, activities or support. [ 43 , 52 , 53 , 57 , 58 , 77 ] QoL, family and significant relationships Environmental events Service characteristics • Presence in catchment areas with high levels of refugees and asylum seekers. [ 29 ] • Community engagement projects focused on asylum seekers and refugees.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co‐location is a feature of many youth mental health services, with ‘youth hubs’ and ‘one stop shops’ used to address barriers to accessing care (Abba‐Aji et al, 2019; Hilferty et al, 2015; Hodgekins et al, 2017; McGorry et al, 2019; Morgan et al, 2019; Parabiaghi et al, 2019). hEIT is co‐located within a youth and family‐friendly headspace setting, with access to collaborative services, and was perceived by clinician participants as more accessible for young people than specialist mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…New models of care featuring low stigmatizing youth‐friendly services to improve access, with primary and secondary prevention goals, have been developed internationally, including Australia (Hilferty et al, 2015; Orygen, National Centre of Excellence in Youth Mental Health, 2018), Canada (Abba‐Aji et al, 2019), Italy (Parabiaghi et al, 2019), New Zealand (Morgan et al, 2019) and the United Kingdom (Hodgekins et al, 2017). A 2019 review of youth mental health ‘hubs’, found common principles including rapid access to evidence based care, youth‐friendly services and settings, youth and family engagement, and partnerships and collaboration (Settipani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%